Globalisation of environmental protection: future challenges for Malaysian businesses - Kadaruddin Aiyub,; Gerrard, S,; Martin, A, (Environmental Management Society, Malaysia, 2006)
Globalisation has been defined as intensification of worldwide social relation which link distant localities in such a way that local happenings are shaped by events occurring many miles away and vice versa. Globalisation has been viewed in different ways – pros and cons - but insofar as environmental management perspectives is concerned, it is thought as the best way to protect the environment for human use. This is done by adopting common standards through a framework where goals and resources that are managed on a global scale being applied through decisions made locally. Several researchers have identified that globalisation of environmental protection has an impact on international trade and local businesses. Almost all of developing countries are dependant on their export to Western world especially to European Union and the United States where environmental concern on goods and products is high. Malaysia in particular has been involved in many multilateral environmental agreements (MEAs) and voluntary initiatives for environmental protection. At the regional level, ASEAN and APEC for example, have passed a number of declarations on environmental protection, which reveal their intention to safeguard the environment. This is a new challenge in doing businesses in the era of globalisation. This article highlights on Malaysia’s responses to global environmental initiatives and their implication on international trade and domestic economy